CHARACTER BUILDING AND LITERACY CULTURE IN PRIMARY EDUCATION (Case Study in SMPN 1 Tulungagung) - Arifin, Muh Zainul (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2020)
Â ABSTRACTCharacter building and literacy culture is urgent something and must be done by educational institutions, especially primary educations. In primary education , students are accustomed to good behavior, so that in the end they have good character. Indeed, character building is not easy and cannot be instantly, but with continuous habituation it will produce a character output. This research is qualitative in nature with a type of case study that has a single case study design. This research is qualitative research in education so to understand external reason of character building and literacy culture. The results of this study are the building character and literacy culture in educational institutions carried out in several stages. This research adds a new variant to Kaizen theory, which is intangible value. This research also adds a new variant to the theory of Ndraha, namely the synergy of all citizens of educational institutions and the active role of intangible values.Â Keyword: Character Building, Literacy Culture, Primary Education